BIOFEEDBACK AND MODERN CLINICAL PRACTICE - Kulik, A. L.; Yabluchansky, N. I. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
In the review the technology of biofeedback is examined ― promising direction in modern clinical medicine. The history of the method and variants of the technical implementation of the contours of biofeedback is described. The efficiency of the method in clinical practice on the example of chronic heart failure is discussed.